Tying up tranylcypromine: Novel selective histone lysine specific demethylase 1 (LSD1) inhibitors - Ji, Y.; Lin, S.; Wang, Y.; Su, M.; Zhang, W.; Gunosewoyo, Hendra; Yang, F.; Li, J.; Tang, J.; Zhou, Y.; Yu, L. (Elsevier Masson, 2017)
© 2017 Elsevier Masson SAS Aberrant expression of lysine specific histone demethylase 1 (LSD1) has been increasingly associated with numerous cancer cells and several proof-of-concept studies are strongly suggestive of its potential as a druggable target. Tranylcypromine (TCP) is an antidepressant originally known to target the monoamine oxidases A and B (MAO-A and MAO-B), which are structurally related to LSD1. A number of TCP derivatives have been identified as potent LSD1 inhibitors, with a handful of them currently being tested in clinical trials. However, thus far the majority of structure-activity relationship studies reported on these TCP derivatives have been mostly limited to the racemates. In this study, we present the SAR data for a novel series of conformationally-restricted TCP-based LSD1 inhibitors, both in their racemic and enantiomerically pure forms. Compounds 18b and 19b were identified as the most potent LSD1 inhibitors within this series, possessing excellent selectivity ( > 10,000-fold) against MAO-A and MAO-B. These compounds activated CD86 expression on the human MV4-11 AML cells following 10 days of exposure, accompanied with the apparent cytotoxicity. Taken together, these findings are consistent with the pharmacological inhibition of LSD1 and further provide structural insights on the binding modes of these TCP derivatives and their enantiomers at the LSD1.